AS AUDIÊNCIAS PRELIMINARES DE CONCILIAÇÃO E MEDIAÇÃO NAS DEMANDAS FAMILIARES E O DIREITO DE ACESSO À JUSTIÇA: Uma análise das percepções e das práticas do Poder Judiciário maranhense para solução de conflitos e superação de crises institucionais - ROCHA, Maricy Ribeiro Fideles (2021)
The present study is dedicated to the evaluation of the practices and perceptions of the institutional actors of the Public Power in relation to the National Judicial Policy of adequate treatment of conflicts of interests in the scope of the Judicial Power in the family demands. To this end, the newsletter makes use of the bibliographic research methodology, with an explanation of the reasons why Public Policy was conceived and instituted, a saber, the evolution of the concept of fundamental right to access to justice and the change of the concept of jurisdiction. It takes a look at the history and objectives of the reforms previously printed by the Government, in order to attack the systemic crisis of the Judiciary and the impact of these on the demands related to Family Law. Subsequently, using the documentary and bibliographic research method, it analyzes the normative regulations of the Policy (these being CNJ Resolution No. 125/2010; the changes brought by Law 13.105 / 2015 - The New Civil Procedure Code and Law 13.140 / 2015 - The Law of Mediation) in order to identify the guidelines and the mode of action planned for the execution of the program. Finally, it investigates the conformation between the objectives of the policy, its guidelines and instructions for the performance and perception of the intuitive subjects of the justice system, especially the conciliators and judicial mediators, through the methodology of analysis of applied teaching content.